The reach of jobseeker rights to free movement: On the complementary relationship between primary and secondary law - Mads Andenas; Tarjei Bekkedal (Oslo Law Review)
The reach of jobseeker rights to free movement depends on the relationship between norms at different levels of European Union (EU) law. The default methodological approach to these norms misapplies the conflict of norms doctrine in constitutional theory. Rights are read down based on an analysis of how the norms relate to, reinforce or otherwise affect each other as parts of a hierarchical whole. We advance a different approach and take as our starting point that the fundamental status of a jobseeker is that of Union citizen. Union citizens have a plethora of rights that are complementary. Citizens may optimise their legal position by invoking, or not invoking, rights. In the first place, courts and other judicial authorities must make sense of the actual choice made by the Union citizen rather than any abstract hierarchy of norms. We analyse the rights of jobseekers to reside in the host state, to export unemployment benefits for a period greater than the three months granted by Regulation 883/2004, and to retain unemployment benefits when they stay in a state other than the competent state without any intention of seeking work there. Our approach shows that the Court of Justice of the EU has resolved these matters in an entirely coherent manner.